Single phase grid interconnected high gain boost converter with soft switching capability - Bogimi Sirisha; Akhilesh Saieni (International Journal of Advances in Applied Sciences, 2022)
The grid-interconnected application systems require high voltage levels which leads to an efficiency reduction. To overcome this, a new high gain boost converter in association with a buffer capacitor, and passive clamp recovery circuit to restore leakage energy in coupled inductor is presented. The magnetic field of the linked inductor stores the energy obtained from the supply. The energy is transmitted to the connected load for consumption in further operating modes. A passive clamp network recovers the energy that is stored in the leakage inductance, enhances the gain of voltage, and improves overall system efficiency. The essential feature of this converter is that, high duty ratios are not required to achieve higher voltage gain, hence the reverse recovery problem of the diode is prevented. Moreover, a passive clamp network decreases the voltage stress of the switch, thus a minimum rating switch is used, as a result, the system's total efficiency improves. This converter output is fed as input to a single-phase full-bridge inverter and also synchronized to a single-phase grid. The performance and powers injected are analyzed by connecting a resistive load.